Genetic algorithm for solving dynamic simultaneous route and departure time equilibrium problem - Li, Shu-Guang (Transport, 2008)
We present a genetic algorithm for solving dynamic simultaneous route and departure time equilibrium problem. Not only can a flow‐swapping process in the algorithm guarantee the flow conservation constraints between OD pair, but also accelerate the convergence velocity of the algorithm. Finally, a simulation example shows feasibility and validity of genetic algorithm. First published online: 27 Oct 2010